Evaluation of patient decision aid for opportunistic salpingectomy and salpingectomy as sterilization method to prevent ovarian cancer. Issue 28 (1st October 2022) - Gelderblom, Malou; Piek, Jurgen M.J.; Briet, J; Bullens, Lauren; Coppus, Sjors; Ebisch, Inge; van Ginkel, Alexandra; van de Laar, Rafli; de Lange, Natascha; Ngo, Huy; Maassen, Marloes; Oei, Angele; et al.
Abstract : 379 Background: The fallopian tubes play an important role in the pathogenesis of epithelial ovarian cancer. This has led to recommendations for performing bilateral salpingectomy as primary prevention of ovarian cancer, the opportunistic salpingectomy (OS). OS has gained territory globally, however with unwanted practice variation. Since all women have the right to be informed on OS, a patient decision aid (PtDA) on OS and salpingectomy as sterilization method has been developed to provide uniform counseling and reduce this practice variation. The aim of this study was to evaluate the effect of the PtDA on the decision-making process. Methods: As part of the STOPOVCA-implementation-study we conducted a multicenter observational prospective study between July 2020 until now. Women who were eligible for OS were invited to use the PtDA while they considered whether or not to undergo OS during gynecological surgery. Evaluation was performed using digital questionnaires regarding their decision, the decision process, and the PtDA. Preliminary. Results: In total 84 women participated to the questionnaire of which 71 used the PtDA. The majority chose to undergo OS (90%). Main reasons for women choosing OS were the risk reducing effect of ovarian cancer and the unnecessary preservation of the fallopian tubes after childbearing. After using the PtDA, from patients perspective the extent to which they were involved in the decision-making process was high, and the decisional conflict low. Patients thought it is a usable aid and recommend other women who face the decision regarding OS to use it with an 8.4 out of 10. Conclusions: The PtDA supports the decision-making on whether or not to undergo OS among patients who have completed childbearing and undergo abdominal gynecological surgery.